2017
DOI: 10.1021/acs.inorgchem.6b03134
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Octahedral Magnetic Molecules Based on [NbIV(CN)8]4–

Abstract: A building block approach has been used to prepare a new family of hexanuclear magnetic molecules MnNb, FeNb, and CoNb of general formula {[M(tmphen)][Nb(CN)]}·solv (M = Mn, Fe, Co; tmphen = 3,4,7,8-tetramethyl-1,10-phenanthroline; solv = MeOH and/or HO). MnNb exhibits a magnetocaloric effect at temperatures close to 1.8 K, and FeNb undergoes an incomplete gradual spin crossover and a photomagnetic response related to light-induced excited spin state trapping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 83 publications
3
21
0
Order By: Relevance
“…The pressuredependentg raduald ecrease of the c M T in the 300-80K range can be ascribed to the pressure-induced spin crossover (SCO) of ac ertain fraction of Fe II HS centres (S HS = 2) to the low-spin diamagnetic state (S LS = 0). The gradualand incomplete character of the SCO was observed previously for similar clusters, [33,34] Fe 4 grid compounds [52,53] and trigonal bipyramidal molecules. [54] Note that the shapes of the SCO curvesp resented in Figure 10 and Figure S16 are also affected by the gradual pressure drop inside the pressure cell (usually around0 .15 GPa in the 300- 50 Kr ange) due to the solidificationo ft he pressure transmitting medium Daphne 7373.…”
Section: Magnetic Properties Under Pressuresupporting
confidence: 78%
See 1 more Smart Citation
“…The pressuredependentg raduald ecrease of the c M T in the 300-80K range can be ascribed to the pressure-induced spin crossover (SCO) of ac ertain fraction of Fe II HS centres (S HS = 2) to the low-spin diamagnetic state (S LS = 0). The gradualand incomplete character of the SCO was observed previously for similar clusters, [33,34] Fe 4 grid compounds [52,53] and trigonal bipyramidal molecules. [54] Note that the shapes of the SCO curvesp resented in Figure 10 and Figure S16 are also affected by the gradual pressure drop inside the pressure cell (usually around0 .15 GPa in the 300- 50 Kr ange) due to the solidificationo ft he pressure transmitting medium Daphne 7373.…”
Section: Magnetic Properties Under Pressuresupporting
confidence: 78%
“…Among them, cyanido-bridged octahedral clusterso ft he general formula {[M1 II reveal photomagnetism, [28][29][30][31] {[Mn II (bpy) 2 ] 4 [Nb IV (CN) 8 ] 2 } [32] and {Mn II [33] presents spin crossover behaviour andp hotomagnetism related to the lightinduced excited spin state trapping effect (LIESST) at the Fe II centres,{ [Fe II (tmphen) 2 ] 4 [Mo IV (CN) 8 ] 2 } [34] presents site-selective photoswitching and {[Co II (tmphen) 2 ] 4 [Nb IV (CN) 8 ] 2 } [33] [35] demonstrate photomagnetic behaviour and single-crystal-to-single-crystal( SCSC)t ransformations-a rare phenomenon among discrete molecular systems. [36] TheS CSC transformations in the purely molecular Cd 4 Mo 2 and Cd 4 W 2 are relatedt ot he reversible release and sorption of water molecules by their crystals, resembling the behaviouro fs ome metal-organicf rameworks (MOFs).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24]. Among octacyanometallates one can find slowly relaxing systems [25][26][27], guest-molecule absorptive porous networks [28,29], photomagnets [30,31], and magneto-optically active compounds [32], as well as molecular sponges, which change, in a reversible way, the ordering temperature T c and the coercive field H c upon hydration/dehydration process [33] and other functional materials [34]. Below, we discuss the magneto-thermal properties of the octacyanometallates showing the different types of crystal architecture.…”
Section: Introductionmentioning
confidence: 99%
“…[6c,8] Va luable switching properties were presented for Fe II SCO materials incorporating [M IV/V( CN) 8 ] 4À/3À (M = Nb,M o, W, Re) metalloligands. [9,10] In particular,t he [Nb IV (CN) 8 ] 4À ion produced with Fe II (L) (L = pyridine or pyrazole derivatives) complexes the 3D Fe-Nb cyanido-bridged networks exhibiting such physical phenomena as light-induced ferrimagnetism, [9c] a908 8 photoswitching of the second harmonic polarization plane, [9d] and ap ressure-induced SCO photomagnetism. [9f] Fe 2+ and [M IV (CN) 8 ] 4À ions were employed for the construction of SCO-active {Fe II 4 M IV 2 }c lusters and as ite-selective photoswitching of Fe II -orMo IV -centered spin-transition routes was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…[9f] Fe 2+ and [M IV (CN) 8 ] 4À ions were employed for the construction of SCO-active {Fe II 4 M IV 2 }c lusters and as ite-selective photoswitching of Fe II -orMo IV -centered spin-transition routes was achieved. [10] Surprisingly,the magnetic switches based on Fe II -[M IV (CN) 8 ] 4À systems suffer from poor SCO cooperativity and difficulty in achieving stepwise spin transitions.While we have shown that the multistep SCO effect can be induced in the 3D Fe II -M IV (M = Mo,Nb) networks by amethod utilizing in situ ligand transformation giving three non-equivalent Fe II sites,agradual course of SCO remained. [9h] These disadvantages are due to the robust character of the 3D Fe II -M IV networks and weak supramolecular interactions between {Fe II 4 M IV 2 }molecules;both effects hamper elastic interactions between Fe sites.O ur idea to overcome these difficulties consisted of the application of [M V (CN) 8 ] 3À (M = Mo,W ,Re) ions whose (3À)charge favors the formation of more flexible cyanido-bridged coordination polymers with rich non-covalent interlayer interactions.…”
Section: Introductionmentioning
confidence: 99%